002.2 Operational performance of a new molecular-based point-of-care test for diagnosis of chlamydia trachomatis and neisseria gonorrhoeae infection: concordance with conventional laboratory testing. (13th September 2015) - Causer, LM; Tangey, A; Badman, SG; Hengel, B; Natoli, L; Speers, D; Tabrizi, SN; Whiley, D; Anderson, DA; Ward, J; Kaldor, JM; Guy, RJ
Abstract : Introduction: New molecular-based point-of-care (POC) tests for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections are being used for the first time by trained Aboriginal health workers/practitioners, registered/enrolled nurses and medical officers in regional/remote health services in Australia as part of TTANGO (Test, Treat ANd GO). We assessed the operational performance of the GeneXpert®CT/NG assay (Cepheid) POC test using conventional laboratory tests as the reference standard. Methods: TTANGO, a randomised cross-over control trial of CT/NG POC testing, commenced June 2013. To date, 12 services have implemented GeneXpert testing on-site as routine practice, with specimens still sent to jurisdictional laboratories for conventional nucleic acid amplification testing (NAAT) as usual. We assessed the concordance of GeneXpert performed by health service staff with conventional laboratory NAAT. We also present selected details of discordant specimens. Results: Among 1995 GeneXpert tests performed, CT and NG were detected in 182 and 127, respectively, by the jurisdictional laboratory. CT concordance was 99.4% (95% CI: 99.0 – 99.8) and NG was 99.9% (99.6–100.0). The fourteen discordant results (eight urines, six lower vaginal swabs) were identified in seven services and five laboratories (two use Cobas 4800, three use Aptima). Discordant results were predominantly CT (n = 12) and most (n = 10) were positive POC/negative laboratory results. The median POC test crossing point among CT discordants was 37.2 (IQR: 31.6–37.7) with five of nine (55.6%) having crossing points >35, compared to 29.2 (IQR: 26.3–32.6) among CT concordants with 10 of 179 (5.5%) having crossing points >35. The two NG discordant results were both positive POC/negative laboratory results. Conclusion: The performance of GeneXpert in the hands of trained health service staff is excellent and consistent with previous laboratory and field evaluations. Higher crossing points of discordant results most likely indicates low organism loads close to test detection threshold and seem unrelated to service, laboratory, specimen type or reference assay. Overall, results show the GeneXpert method is suitable for routine detection of CT and NG. Disclosure of interest statement: No conflicts of interest declared. No financial support was received by Cepheid. Cepheid has provided GeneXpert devices on loan for the duration of TTANGO and test cartridges at a reduced rate.